Development of General Election Services for Disabilities by using Application SUARAKU In Surabaya - Saidatin, Naili; Munir, Misbakhul; Oktaviani, Mayang Viorita; Tulus Widodo, Putut Giri (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2019)
One form of democracy in Indonesia is a general election to determine every leader in a region. As an election participant not all people have the same ability, one of them is disability people who still often find it difficult to take part in elections. Some people with disabilities in Surabaya are blind, deaf and illiterate. To support the disability following the general election in Surabaya an application called SUARAKU was created. SUARAKU is an application based on Android mobile that can help people with disabilities, especially blind, illiterate and deaf in identifying candidate pairs, track record, mission vision and campaign schedule of the candidate pairs. SUARAKU can help people with disabilities in the form of sounds and images. The voice used consists of two kinds of languages, namely Javanese and Indonesian which aims to facilitate the users of this application. With the existence of the SUARAKU application, it is expected to support the achievement of the disability rights to participate in voicing their rights and obligations in order to create a just and prosperous IndonesiaKeyword: general election, disability, android